Variation in Fibre Length, Vessel Length and Ray Height of Sixteen Tree Species Occurring in Mangrove Forests of Bangladesh - Mariam, Hasina; Paul, Asim Kumar; Jahangir Alam, A. H. M. (Indian Forester, 2018)
Anatomical features like fibre length, vessel length, and ray height was studied on sixteen mangrove species growing in the Sundarbans of Bangladesh. The results of the study show that the fibre length of the sixteen species varies from 0.37 mm to 1.12 mm, with the highest in Barringtonia racemosa (1.12 mm) while vessel length varies from 0.15 mm to 1.12 mm with the highest in Randia wallichii (1.12 mm). Variation in ray height among the species ranges from 0.21mm to 2.45mm. The highest ray height was found in Randia wallichii (2.45 mm). The study shows a gradual increase of fibre and vessel length from near pith to periphery. No such variation was found in case of ray height.